LANGUAGE LEARNING THROUGH AI TECHNOLOGIES - Yusupova Sevinch Sherzod qizi (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This paper explores the growing role of artificial intelligence (AI) in language learning, highlighting its potential to transform traditional educational methods. AI-powered applications, such as chatbots, virtual tutors, and speech recognition systems, offer personalized, interactive, and adaptive learning experiences that cater to individual needs and learning paces. These technologies can enhance vocabulary acquisition, grammar comprehension, pronunciation accuracy, and conversational skills. The integration of AI in language education not only increases learner engagement but also provides real-time feedback and continuous progress tracking. This abstract discusses the current applications, benefits, and challenges of using AI in language learning, aiming to provide insights into its effectiveness and future prospects.